Genome-wide exploration of beneficial Bacillus subtilis isolate from resistant banana cultivar Anaikomban towards the management of Fusarium wilt in banana - B.R. Ajesh; P. Renukadevi; N. Saranya; N. Vidhyashri; S. Varanavasiappan; S. Vellaikumar; Suhail Ashraf; S. Haripriya; Mohammad Raish; S. Nakkeeran (Journal of Agriculture and Food Research)
Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense (Foc), severely impacts global banana production, urging the development of sustainable management strategies. This study conducted a comprehensive genome-wide exploration of a beneficial Bacillus subtilis isolate AKPS2 obtained from the resistant banana cultivar Anaikomban, with potential biocontrol capabilities against Foc. Through an integrated approach combining in vitro screening, whole genome sequencing, pangenome analysis, and advanced molecular docking techniques, we investigated the antimicrobial mechanisms of this bacterial endophyte. Initial in vitro dual culture assays revealed the isolate's robust antagonistic activity against Foc, inhibiting the fungal growth by 61.11 %, which prompted further genomic investigation. Whole genome and pangenome analyses identified the genetic repertoire underlying the isolate's biocontrol traits including antimicrobial peptides (AMPs) such as surfactin, bacillibactin, fengycin. Molecular docking identified surfactin as the most potent AMP, exhibiting the highest binding affinity (−12.1 kcal/mol) to key Foc target proteins. Furthermore, screening using the poison food technique confirmed the antifungal activity of surfactin, achieving an inhibition rate of 85 % against Foc in vitro, thereby validating the computational predictions. This comprehensive study highlights the genome-driven discovery and functional characterization of B. subtilis as a promising biocontrol agent, paving the way for sustainable management of Fusarium wilt in banana cultivation.